Investigation of metamaterial unit cells based on dispersion characteristics - Nur, Abdirashid Mohamed; Wan Nordin, Mimi Aminah; Islam, Md. Rafiqul; Habaebi, Mohamed Hadi (Asian Research Publishing Network (ARPN), 2015)
Metamaterials are artificial effectively-homogenous electromagnetic structures with properties that are not readily available in nature, they are periodic structures made up of unit cells. While the field of metamaterial is receiving much interest, not too many researches have been done to characterize the metamaterial. A few metamaterial unit cells are chosen to characterize and investigate the propagation of EM waves inside the metamaterial, eigenmode solver in Computer Simulation Technology Microwave studio (CST MWS) has been used to derive the dispersion diagram. We found that some unit cells produce pure left-hand (LH) propagation while the others produced composite right/left-handed (CRLH) propagation. It is also proposed for the unit cells that can be used for wireless applications.